Facilitating a Public SoTL Writing Group: For the Public or with the Public? - Ultsch, Sharon; Ford, Catherine (Teaching and Learning Inquiry, 2025)
The concept of public SoTL, aimed to extend the field’s influence beyond academia, challenged writing group facilitators to redefine their expectations and actions as traditional approaches fell short, prompting a reevaluation. This essay chronicles the journey of the facilitators in the inaugural ICWG-Public SoTL cohort, exploring what it means to facilitate a project with influence beyond academia. The facilitators of this public SoTL writing group encountered numerous challenges, including redefining their roles and expectations, engaging with public audiences, and applying critical pedagogy frameworks. This reflective essay shares their facilitation story and the importance of understanding public SoTL’s purpose, audience, and products, which led to a framework for future ICWG-Public SoTL facilitators. Their public SoTL facilitation framework with a critical lens emphasizes the need for a collaborative, iterative approach that prioritizes the needs of the public over traditional academic outputs, ultimately advocating for a more inclusive and impactful form of scholarship.